La inversión de la carga de la prueba: la experiencia latinoamericana peruana - Varsi-Rospigliosi, Enrique (2006)
In Peru, the Law N° 28457 (08/01/2005) regulates the action to stablish the filiation. In this way, the presumed father is declared by sentence father of the child. The only way to contest the action – within next ten days since the notification of the action – is to submit to the DNA analysis.